2021
DOI: 10.3390/ph14060531
|View full text |Cite
|
Sign up to set email alerts
|

PESIN Conjugates for Multimodal Imaging: Can Multimerization Compensate Charge Influences on Cell Binding Properties? A Case Study

Abstract: Recently, anionic charges were found to negatively influence the in vitro gastrin-releasing peptide receptor (GRPR) binding parameters of dually radioisotope and fluorescent dye labeled GRPR-specific peptide dimers. From this, the question arose if this adverse impact on in vitro GRP receptor affinities could be mitigated by a higher valency of peptide multimerization. For this purpose, we designed two different hybrid multimodal imaging units (MIUs), comprising either one or two click chemistry-compatible fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Taken together, these data demonstrate that the conjugation of the MIUs to the monomeric PESIN peptide results in principle in only a minor reduction of binding affinity of the conjugates, which were still able to specifically interact with the GRPR with high affinity and the negative influence of anionically charged fluorescent dyes on GRPR binding affinities was confirmed. As expected, the adverse influence of the negatively charged dye on GRPR affinities was more pronounced in case of the peptide monomer compared to the peptide homodimer, confirming the theory that a higher number of peptide copies within the bioconjugates is at least in part able to compensate the adverse effect of the negative charge of the dye [22].…”
Section: Determination Of the In Vitro Receptor Binding Affinities Of The Hybrid Peptide-miu-bioconjugatessupporting
confidence: 82%
See 1 more Smart Citation
“…Taken together, these data demonstrate that the conjugation of the MIUs to the monomeric PESIN peptide results in principle in only a minor reduction of binding affinity of the conjugates, which were still able to specifically interact with the GRPR with high affinity and the negative influence of anionically charged fluorescent dyes on GRPR binding affinities was confirmed. As expected, the adverse influence of the negatively charged dye on GRPR affinities was more pronounced in case of the peptide monomer compared to the peptide homodimer, confirming the theory that a higher number of peptide copies within the bioconjugates is at least in part able to compensate the adverse effect of the negative charge of the dye [22].…”
Section: Determination Of the In Vitro Receptor Binding Affinities Of The Hybrid Peptide-miu-bioconjugatessupporting
confidence: 82%
“…To be more specific, it was found that the higher the number of negative charges in the selected dye was, the worse the resulting binding affinity to the targeted receptor. This concept was confirmed using diverse PESIN-homodimer conjugates presenting different dye units [20,21], as well as with a PESIN-homotetramer conjugate, being characterized by a higher peptide valency [22]. In this latter case, it was interestingly observed that the adverse influence of the negatively charged synthons on the target receptor affinity was in part compensated by the higher number of peptide units in the molecule, arguing a possible intramolecular spatial shielding effect of the peptides on the adverse charges.…”
Section: Introductionmentioning
confidence: 70%
“…Therefore, it was assumed that the higher the number of anionic charges carried by the conjugate (being determined by the fluorescent dye used), the lower the resulting GRPR binding affinity of the resulting multimodal imaging agent. This theory was confirmed upon various PESINmonomer conjugates [1] presenting different dye units, as well as with the corresponding PESIN-homodimer [3,4] and -homotetramer [2] conjugates. By comparing the binding profiles within these series, it was also observed that the GRPR affinities of the conjugates carrying a higher number of peptide copies were less affected by the anionic charges of the introduced fluorescent dyes than their corresponding conjugates exhibiting a lower peptide valency.…”
Section: Introductionsupporting
confidence: 57%
“…This was demonstrated by analyzing the absorption spectra of the two compounds at the fixed pH value of the medium (measured pH of 8.23): both spectra presented main absorption peaks at 496/498 nm, with a shoulder around 475 nm, corresponding to the di‐anionic proteolytic form of fluorescein, being in line with data reported in literature. [18] As confirmation, in the context of the charge‐cell binding correlation, the PESIN dimer derivative 2 a showed a GRPR binding affinity comparable to other dimeric PESIN conjugates carrying two anionic charges within the dye moiety,[ 2 , 3 ] including the tartrazine‐based conjugate 2 b being evaluated under the same conditions for direct comparison (IC 50 values of 62.07±3.87 nM and 58.44±1.47 nM for 2 a and 2 b , respectively; Table 1 ). These results demonstrate a clear correlation between the number of negative charges carried by the dye molecule within multimodal imaging agent and its GRPR binding properties.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation